The Effect of Deep Respiration and Prone Position on Common Respiratory Symptoms in Patients with COVID-19: A Randomized Clinical Trial - Sima Alipour Nasrabadsofla; Afshin Mansourian; Mohammad Gholamnezhad; Ardashir Afrasiabifar; Asadolah Mosavi; Shahla Najafi Doulatabad (Iranian Journal of Nursing and Midwifery Research)
Background: COVID-19 causes many respiratory problems. The most common clinical manifestation is acute respiratory failure. Respiratory rehabilitation is an important part of treatment, but little is known about it. This study was carried out to determine the effect of deep respiration and prone position on common respiratory symptoms in patients with COVID-19. Materials and Methods: In this clinical trial that was conducted in a hospital in Yasuj city, Iran, in 2021, 96 patients with COVID-19 were selected using a non-random convenience sampling method and were randomly assigned to three groups of deep respiration, prone position, and deep respiration and prone position. Data were collected using the Borg Rating of Perceived Exertion scale, the Visual Analog Scale, pulse oximetry, and a researcher-made checklist of patients’ respiratory rates. The interventions were performed for 1 week (2–8 hours daily) based on patient tolerance. Data were collected before and immediately after the intervention. Results: There was no statistically significant difference (p > 0.05) among the three groups in terms of mean score of shortness of breath, intensity of symptoms, oxygen saturation of blood, and respiration rate before the interventions; however, significant differences were observed after the interventions (p < 0.05) in the three groups. Conclusions: Deep respiration with prone position could improve respiratory symptoms in patients with COVID-19 more than deep respiration or prone position alone. Respiratory exercise should be considered as a part of nursing cares and patients with respiratory symptoms should receive education in this regard.